2019
DOI: 10.14302/issn.2642-9241.jrd-19-2667
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pneumonia: Biological Rules and Laws require Attention and Respect.

Abstract: Various aspects of human life proceed according to the existing biological rules and laws regardless of our consciousness. The influence of such biological stereotypes is manifested in all possible situations, including in the state of disease. The presence of certain patterns in the development of diseases allows them to distinguish and classify. The identification of such biological patterns was given great importance throughout the history of medicine, and established and proven facts were immediately inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The discrepancy between the dominant assumptions and the actual facts is becoming more pronounced every year. Therefore, the main conclusion of this review should be made first of all about the need to revise the doctrine of САР [11][12][13]. I hope that the authors of the analyzed article will be able to correctly understand the meaning of my comments and in case of questions will be able to count on the answer and additional explanations.…”
Section: Dear Colleaguesmentioning
confidence: 97%
“…The discrepancy between the dominant assumptions and the actual facts is becoming more pronounced every year. Therefore, the main conclusion of this review should be made first of all about the need to revise the doctrine of САР [11][12][13]. I hope that the authors of the analyzed article will be able to correctly understand the meaning of my comments and in case of questions will be able to count on the answer and additional explanations.…”
Section: Dear Colleaguesmentioning
confidence: 97%
“…However, over the past period, there have been enough changes that clearly demonstrate the declarative nature of the infectious concept of AP and expand the audience of specialists who have lost faith in the panacea of antibiotics. Therefore, the urgent need for a critical reassessment of the nature of the disease [9] will allow for a more rational use of care and not expect much success when continuing vaccination against pneumonia.…”
Section: Advances In Pediatric Researchmentioning
confidence: 99%
“…Modern ideas about the nature and mechanisms of AP development, based on an overestimated assessment of the role of the microbial factor in the interpretation of any negative consequences of the disease, narrow the direction of research on this problem and make it difficult to find scientific explanations for the observed contradictions between theory and practice. The only way out of this impasse is through a radical revision of the AP doctrine, since the explanation of such discrepancies depends on the influence of already known and generally accepted biological rules and laws (6). Meanwhile, in the light of the above, when evaluating the results of correction of terminal States, it seems necessary to distinguish a group of patients with AP into a separate one, which will allow analyzing therapeutic actions in the conditions of a unique mechanism of the disease.…”
mentioning
confidence: 99%